2010
DOI: 10.1007/bf03395712
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Impact of Skinner’s Verbal Behavior on Empirical Research: A Reply to Schlinger (2008)

Abstract: In a recent article, Schlinger (2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…For most behavior analysts, the answer has been in the affirmative (e.g., Palmer, 2006a)" (Schlinger, 2008a, p. 332). Dymond and Alonso-Álvarez (2010) have not, in my opinion, argued convincingly that Skinner's interpretation was inconsistent with the basic principles of behavior. In VB, Skinner classified verbal operants according to the type of antecedent control that determines the form of the response.…”
Section: Consistency Of Interpretationmentioning
confidence: 83%
See 2 more Smart Citations
“…For most behavior analysts, the answer has been in the affirmative (e.g., Palmer, 2006a)" (Schlinger, 2008a, p. 332). Dymond and Alonso-Álvarez (2010) have not, in my opinion, argued convincingly that Skinner's interpretation was inconsistent with the basic principles of behavior. In VB, Skinner classified verbal operants according to the type of antecedent control that determines the form of the response.…”
Section: Consistency Of Interpretationmentioning
confidence: 83%
“…such as those found in relational classes" (p. 206)-that RFT proponents seem to champion. Although there is not sufficient space here, let me just add that I believe that the criticisms of Skinner's definition of verbal behavior have been more than adequately addressed (e.g., Leigland, 1997;Normand, 2009;Palmer, 2008;Schlinger, 2008b). Conformity to Scientific Principles Dymond and Alonso-Álvarez (2010) state that "the interpretation presented in Verbal Behavior does indeed conform to basic scientific principles, but only with those scientific principles available up to 1957" (p. 356) and that some have "raised the intriguing empirical question of whether 'behavioral principles different from those already discovered in research with nonhumans may be needed to explain complex human behavior, most notably in the experimental analysis of verbal behavior' (Dymond et al, 2003, p. 334…”
Section: Consistency Of Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, behavior analysts have found that much of the research derived from Skinner's analysis has focused on a small number of verbal operants (e.g., Sautter & LeBlanc, 2006) and populations with autism and developmental disabilities (e.g., Dixon, Small, & Rosales, 2007), leading some to question the ultimate impact of Skinner's analysis on the study and understanding of language (e.g., Dymond & Alonso-Á lvarez, 2010). This issue is directly related to concerns with the definition of verbal behavior from the perspective of RFT theorists.…”
Section: Skinner's Analysis Of Verbal Behaviormentioning
confidence: 99%
“…In fact, there may be somewhat of a theoretical divide between some behavior analysts and their approaches to language and cognition (e.g., see a recent discussion, Dymond & Alonso-Á lvarez, 2010;Schlinger, 2008). Indeed, there are those who have extended Skinner's analysis (S. C. Hayes et al, 2001), those who seem to adhere closely to it (e.g., Palmer, 2004Palmer, , 2008Schlinger, 2008), and those who integrate multiple perspectives (e.g., Barnes-Holmes, BarnesHolmes, & Cullinan, 2000;Greer & Speckman, 2009;Rehfeldt & Root, 2005;Rosales & Rehfeldt, 2007).…”
Section: Skinner's Analysis Of Verbal Behaviormentioning
confidence: 99%